A novel particleboard using unsaturated polyester resin as a formaldehyde-free adhesive. (1st September 2017) - Li, Ran; Lan, Congrong; Wu, Zhenzeng; Huang, Tengan; Chen, Xiaobin; Liao, Yuehua; Ye, Longfeng; Lin, Xiuduan; Yang, Yuming; Zheng, Yanmei; Xie, Yongqun; Zhuang, Qingping
Highlights: A novel particleboard via using UP resin as formaldehyde-free adhesive is performed. The new FF particleboard reaches national standards and M-1 grade (ANSI A208.1-1999). With and without PF treatment, properties of FF particleboards are changed greatly. PF treated wood particles to improve the interfacial adhesion of wood fibers and UP. The particleboard is low cost, efficient production and formaldehyde free. Abstract: Wood-based artificial panels are still widely used even though they release harmful formaldehyde. In order to protect humans from exposure to formaldehyde, we successfully produced particleboards via surface treatment of wood fibers and using unsaturated polyester resin (UP) as formaldehyde-free adhesive. A phenolic formaldehyde (PF) aqueous solution was utilized to treat the wood particles to make them more compatible. The mechanical properties were investigated to see if the particleboards comply with national standards and M-1 grade (ANSI A208.1-1999). A water absorption test determined the dimensional stability of the FF particleboards. The PF-treated FF particleboards performed several times better than the untreated FF particleboard. Furthermore, the effect of the PF treatment on the interfacial adhesion of wood particles and UP was investigated using SEM, DMTA, and contact angle measurements. The results confirm that PF treatment improves the interfacial adhesion of UP and wood particles. Formaldehyde emission tests found no formaldehyde in the new particleboards. Our proposed low-cost fiber-treatment and efficient board production method may be suited for the commercial production of artificial panels.